Application of Amorphous Indium Gallium Zinc Oxide Thin Film Transistor Biosensors in Creatine Kinase Detection. (2017) - Lu, Hsin-Chun; Chueh, Yu-Ting; Tseng, Ting; Wang, Chung-Yih; Chaou, Chung-Hsien
Abstract: Amorphous indium gallium zinc oxide (a-IGZO) thin film transistor (TFT) biosensors were fabricated by surface modification of the a-IGZO TFT devices and the immobilization of Creatine Kinase (CK-MM) antibodies on the a-IGZO TFT devices. When the fabricated CK-MM a-IGZO TFT biosensors were used to detect CK-MM in the sample, both the field effect mobility and the Ion /Ioff ratio of the a-IGZO TFT devices were found to increase. These results indicate the potential applications for the developed a-IGZO TFT devices in biosensing.